Microalgae at niches of bioelectrochemical systems: A new platform for sustainable energy production coupled industrial effluent treatment. (September 2019) - Sevda, Surajbhan; Garlapati, Vijay Kumar; Sharma, Swati; Bhattacharya, Sourish; Mishra, Sandhya; Sreekrishnan, T.R.; Pant, Deepak
Abstract: Bioelectrochemical system represents a novel technology where the microbial catalytic reaction occurs at bioanode and results in bioelectricity generation from waste and renewable biomass. At the current stage, fossil-based fuel is depleting, so newly sustainable form of renewable energy resources is required, where algal-based biofuel generation provides a new source of energy along with sequestration of atmospheric carbon dioxide, which in turn decreases the global warming issues. This review emphasizes the potential applications of microalgae-based bioelectrochemical systems for renewable power generation, wastewater treatment, CO2 sequestration and value-added products. Moreover, this critical review also highlights the current developments in microalgal MFC integrated systems by discussing the current potential challenges and drawbacks. Highlights: Algal-based BES are idle for power and value-added products generation and WWT Current developments in microalgal-BES have been discussed Highlighted the potential challenges and drawbacks of the Algal-BES's Put forth the future prospects for integration towards industrial operations.